Reexamining the national-philological legacy : quest for a new paradigm? - Biti, Vladimir (Studia imagologica : Amsterdam studies on cultural identity ;, 2014)
Has thinking, working and teaching in terms of national literatures become obsolete in today's globalized world of hyphenated languages, literatures and cultures? Since the rise of modern European national philologies coincided with the emergence of modern European nation-states, does the dissolution of the latter in the European supranational unity imply the suspension of the former? Or we must, on the contrary, consider the fact that today's Europe is not only postnational but, in its re-nationalized East-Central-European part, post-multinational as well, i.e., emerging out of the breakdown of the postimperial state formations such as the Soviet Union, Czechoslovakia and Yugoslavia?